Functional Outcome After Open Reduction and Internal Fixation in Intraarticular Distal Humerus Fracture: A Case Report - Antonius H Pakpahan; Rashida S Djatnika (Asian Journal of Social and Humanities, 2024)
The purpose of this study is to find out functional outcome after open reduction and internal fixation in intraarticular distal humerus fracture. The method used is the case report method. The purpose of this method is to present in-depth information about a particular case, including symptoms, diagnosis, treatment, and results. A 51-years-old male patient presented to the emergency department after injuring his right elbow following motorcycle accident. He had suffered pain, swelling and bruise on his right elbow without neurovascular injury or external wound. Anteroposterior and lateral x rays and 3D CT scan of the right elbow joint showed simple articular and comminuted metaphyseal classified as type 13-C2. The normal range of flexion-extension of the elbow is 0°–145°. The functional range of motion required for daily activities is 30°–130° of flexion-extension and 50° of supination to 50° of pronation. Distal humerus fracture management requires a carefully planned approach. Surgical management by internal fixation is the treatment of choice for these fractures considered for a satisfactory function.